Partnership communities - Bertelli, Anthony Michael; Woodhouse, Eleanor Florence; Castiglioni, Michele; Belardinelli, Paolo (Cambridge : Cambridge University Press, 2021)
We undertake the first quantitative and broadly comparative study of the structure and performance of partnership communities to our knowledge. Our study addresses several important research questions. How connected are the members of partnership communities? How can we understand the quality of the projects a community undertakes? How do political institutions shape their structure and performance? After defining partnership communities as networked communities of private firms which form the consortia that enter into long-term contractual arrangements with governments, we show how they are affected by government demand for partners. We then provide an overview of those factors predicting success in financing projects. Finally, we focus on the political economy of partnership communities. We develop and test theoretical predictions about how national institutions shape partnership communities and the quality of projects. We also investigate voters' preferences over alternative arrangements of infrastructure delivery before drawing out implications for research and practice.
Title from publisher's bibliographic system (viewed on 21 Oct 2021).
Keywords: Public-private sector cooperation; Community development